Elucidation of the mechanism of anti-herpes action of two novel semisynthetic cardenolide derivatives. - Boff, Laurita; Schneider, Naira Fernanda Zanchett; Munkert, Jennifer; Ottoni, Flaviano Melo; Ramos, Gabriela Silva; Kreis, Wolfgang; Braga, Fernao Castro; Alves, Ricardo José; Maia de Pádua, Rodrigo; Simões, Cláudia M. O. (Archives of Virology, 2020)
Human herpesviruses are among the most prevalent pathogens worldwide and have become an important public health issue. Recurrent infections and the emergence of resistant viral strains reinforce the need of searching new drugs to treat herpes virus infections. Cardiac glycosides are used clinically to treat cardiovascular disturbances, such as congestive heart failure and atrial arrhythmias. In recent years, they have sparked new interest in their potential anti-herpes action. It has been previously reported by our research group that two new semisynthetic cardenolides, namely C10 (3β-[(N-(2-hydroxyethyl)aminoacetyl]amino-3-deoxydigitoxigenin) and C11 (3β-(hydroxyacetyl)amino-3-deoxydigitoxigenin), exhibited potential anti-HSV-1 and anti-HSV-2 with selectivity index values > 1,000, comparable with those of acyclovir. This work reports the mechanism investigation of anti-herpes action of these derivatives. The results demonstrated that C10 and C11 interfere with the intermediate and final steps of HSV replication, but not with the early stages, since they completely abolished the expression of the UL42 (β) and gD (γ) proteins and partially reduced that of ICP27 (α). Additionally, they were not virucidal and had no prophylactic effects. Both compounds inhibited HSV replication at nanomolar concentrations, but cardenolide C10 was more active than C11 and can be considered as an anti-herpes drug candidate including against acyclovir-resistant HSV-1 strains.